GJB5 association with BRAF mutation and survival in cutaneous malignant melanoma. (1st January 2022) - Scatolini, M.; Patel, A.; Grosso, E.; Mello‐Grand, M.; Ostano, P.; Coppo, R.; Vitiello, M.; Venesio, T.; Zaccagna, A.; Pisacane, A.; Sarotto, I.; Taverna, D.; et al.
Summary: Background Gap‐junctional intercellular communication is crucial for epidermal cellular homeostasis. Inability to establish melanocyte–keratinocyte contact and loss of the intercellular junction's integrity may contribute to melanoma development. Connexins, laminins and desmocollins have been implicated in the control of melanoma growth, where their reduced expression has been reported in metastatic lesions. Objectives The aim of this study was to investigate connexin 31·1 (GJB5) expression and identify any association with BRAF mutational status, prognosis of patients with melanoma and mitogen‐activated protein kinase (MAPK) inhibitor (MAPKi) treatment. Methods GJB5 expression was measured at RNA and protein level in melanoma clinical samples and established cell lines treated (or not) with BRAF and MEK inhibitors (MEKi), as well as in cell lines which developed MAPKi resistance. Findings were further validated and confirmed by analysis of independent datasets. Results Our analysis reveals significant downregulation of GJB5 expression in metastatic melanoma lesions compared with primary ones and in BRAF ‐mutated vs. BRAF ‐wildtype ( BRAF WT ) melanomas. Likewise, GJB5 expression is significantly lower in BRAF V600E compared with BRAF WT cell lines and increases on MAPKi treatment. MAPKi‐resistant melanoma cells display a similar expression pattern compared with BRAF WT cells, with increased GJB5 expression associated with morphological changes. Enhancement of BRAF V600E expression in BRAF WT melanoma cells significantly upregulates miR‐335‐5p expression with consequent downregulation of GJB5, one of its targets. Furthermore, overexpression of miR‐335‐5p in two BRAF WT cell lines confirms specific GJB5 protein downregulation. Reverse transcriptase quantitative polymerase chain reaction analysis also revealed upregulation of miR‐335 in BRAF V600E melanoma cells, which is significantly downregulated in cells resistant to MEKi. Our data were further validated using the TCGA_SKCM dataset, where BRAF mutations associate with increased miR‐335 expression and inversely correlate with GJB5 expression. In clinical samples, GJB5 underexpression is also associated with patient overall worse survival, especially at early stages. Conclusions